If it's not what You are looking for type in the equation solver your own equation and let us solve it.
76=y/6
We move all terms to the left:
76-(y/6)=0
We add all the numbers together, and all the variables
-(+y/6)+76=0
We get rid of parentheses
-y/6+76=0
We multiply all the terms by the denominator
-y+76*6=0
We add all the numbers together, and all the variables
-1y+456=0
We move all terms containing y to the left, all other terms to the right
-y=-456
y=-456/-1
y=+456
| -16=-3u+7(u-8) | | -9d+15=96 | | 4x+15-5x+3=90 | | -9d+15=52 | | X2+2x=72 | | 8x-5=36 | | 1+2z=4z+√5+2z | | -7w+4=-52 | | X2-4x=45 | | -2x+40=1/3x-30 | | 3y+5=y+19 | | 4x+15+5x+3=90 | | 2,5y+14=4,5y | | -4q-12=8 | | 4(2x-3)=4x+3 | | 3k-4=10(k+1) | | 7/2(2x+1/2)=x | | x/7+6=1 | | x2-14=5x | | 2x-14=4x+5 | | 21x^2+21x=96x-36 | | r/4-6=-14 | | 8=3(y+6)+2y | | b/6+11=16 | | 3x-4+5x-12+2x-2=180 | | h/9+6=12 | | 8t=−32 | | -3p-5(3-2p)=5(p-5)-8 | | q/3-2=-17 | | 3x-4+5x-12=2x-2 | | (x+3)2−3=0 | | x=24(2x/60)+120 |